A educação contextualizada como instrumento de inclusão social - Castilho, Antonio Ivan (2011)
The object of education research is contextualized in the metropolitan situation. The main objective of the study is to understand the dimension of possibility of developing such as this proposals in metropolitan areas, such as São Paulo. As the research site was chosen Alavanca Brazil Project, developed in a favela in West Zone of São Paulo, with support from the German government and several German companies operating in Brazil. The methodology used in the research, and as a qualitative data technique for collecting was chosen for the literature review and documentary, which was followed by reflection on their own learning process, especially the relationship with the school teacher in this process . As a technique for collecting data, we used the observation, including participation in the project where the research was performed. It was possible to understand that the project has contributed to the growth of the community and especially to broaden the vision of those that led to its implementation. The project has been also responsible for its development. There are some indicators that show this change, the main one being the fact the project is being conducted with significant community participation